GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 539732977 species occurrences available in GBIF matching the query: All data. The dataset includes 539732977 records from 13079 constituent datasets: 31 records from Regenwasserabfangbecken. 46 records from 8c. 149 records from Wirbach. 101 records from Hoher Stein Kallenhardt. 128 records from Birdrace_turbine_untersee-Konstanz. 56 records from Estetal (Buxtehude). 373 records from Otter survey of Ireland 2004 & 2005. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1238 records from Insect Collection (CeStuBio). 27975 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 13993 records from Herpetology. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 122 records from Stever. 28 records from Hainbachtal bei Oelsnitz / V.. 40 records from Schulhof Liebfrauenschule Oldenburg. 27 records from Zwickau- Schwanenteich. 269 records from BIRDRACE Dithmarscher Deichhühner. 2486 records from Hawaiian Algal Database. 11 records from Plasm bearing foraminifera counts from multinet M31/2_MSN896. 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 397 records from Danish Lacewings (Neuroptera). 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 1000 records from Mollusca Specimens of Oiso Municipal Museum. 21188 records from National Bat Database of Ireland. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 195867 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 114 records from Birdrace-Finkenspötter-München. 92 records from Birdrace-Team_BO-bachter-Bochum. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 63 records from Erft in Selikum (Neuss). 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 5 records from Schulinnenhöfe (Gelsenkirchen). 6325 records from Colección Entomológica de la Universidad de Antioquia. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 228 records from Total foraminifera counts from multinet M31/3_MSN917. 54 records from Total foraminifera counts from M35/1_MSN1057. 87 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1363. 49 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/514-18. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 8 records from Ostracoda abundance of Hole 42-375. 936 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 198287 records from IBF Monitoring of Vascular Plants. 339 records from (Table 6) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 50 records from (Table 4) Abundances of dinoflagellates in DSDP Hole 81-552A. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 20114 records from Molluscus specimens of Toyohashi Museum of Natural History. 8944 records from N3 data of Kiel bay (EurOBIS). 2257 records from South Western Pacific Regional OBIS Data Asteroid Subset (South Western Paci fic OBIS). 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 107 records from Landschaftsschutzgebiet Buchhorst 3. 102 records from BIRDRACE Westfälische Nachtigallen. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 66 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, 63-150 µm. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 370 records from Size of planktic foraminifera at CTD station PS55/051. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 48 records from Nanoplankton abundance at station GeoB2005-5. 11 records from Nannofossil abundance of Hole 10-86. 3 records from Nannofossil abundance of Hole 94-609A. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 8 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/108-1. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 936 records from Bats of Poland. 290 records from Planktic foraminifera counts of sediment core RC11-134. 316 records from Planktic foraminifera counts of sediment core V14-101. 823 records from Planktic foraminifera counts of sediment core V17-165. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 75 records from Faunal assemblage of sediment core GS7603-9. 194 records from Total foraminifera counts from multinet M32/3_MSN958. 94 records from Plasm bearing foraminifera counts from M35/1_MSN1044. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 133 records from Total foraminifera counts of multinet M42/3_MSN1363. 54223 records from Fish Specimens. 1422 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 237 records from Collection Mammalogie - SNSD. 60445 records from Bureau of Rural Sciences National commercial fisheries half-degree data set 2000-2002 (OBIS Australia). 21243 records from Myxomycetes Collection of National Museum of Nature and Science. 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 92 records from Nottekanal, Klasse 7 - 10. 67725 records from Patterns of widespread decline in North American bumble bees. 73 records from Planktic foraminifera abundance of Hole 2-11. 163 records from Range table from planktonic foraminifers in ODP Hole 175-1083A. 228 records from Phytoplankton abundance in surface water in June 1997, Pisco, Peru. 11 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 5468 records from Orchid Herbarium Collection. 4 records from A new platygastrid wasp from Florida (Hymenoptera: Platygastridae).. 181 records from Total foraminifera counts of multinet M21/6_MSN766. 9 records from Microzooplankton abundance and biomass at station TT043_6-1. 122 records from Phytoplankton abundance at station CD46_1005C#4. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 89 records from (Table 3) Dinoflagellate cysts from sediment profile PS1730. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 42920 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 56 records from Nanoplankton abundance at station GeoB2021-3. 3 records from Nannofossil abundance of Hole 31-301. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 18 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 367 records from ARKO. 29 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Baerbel Bleher. 126 records from Kelp rafts in the Southern Ocean. 9281 records from Distribution of planktic foraminifers of core V30-40. 10591 records from Planktic foraminifera (%) of sediment core MD97-2151. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 1611 records from Percentages of planktonic foraminifera species in sediment core RC13-189. 42 records from sbosch. 76 records from Total foraminifera counts of multinet M36/2_MSN1107. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 29 records from Counts (1) of calcareous dinocysts along profile Stevns-Klint. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_832-7. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 19 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_7-CTD84. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 9 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/049-3. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 18 records from Phytoplankton abundance at station Rigel_6_2005-04 in April 2005, Chipana, Chile. 261 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Orthoptera Records up to Dec 2012. 482 records from Kühmark bei Wetzlar. 29 records from Schulaktion des Dienzenhofer-Gymnasiums. 2 records from Nannofossil abundance of Hole 3-21A. 694 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 1339 records from Percentages of planktonic foraminifera species in sediment core V25-75. 2 records from Composition of the larger coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 1139 records from Shellfish (MNHM-MS). 114357 records from Data on moths from automatically operating light traps in Denmark. 801 records from Collection Porifera - ZMB. 432 records from (Table 3) Occurrence of dinocyst species in ODP Hole 113-692B. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 1194 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-29. 940 records from Planktic foraminifera distribution of sediment core CS72-37. 133 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 58 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV24. 65 records from Occurrence of mammalia relicts at site L´Abri Duruthy. 13 records from Occurrence of mammalia relicts at site Trou du Renard. 74 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 19 records from Occurrence of mammalia relicts at site Vraona Cave. 22 records from Occurrence of mammalia relicts at site Igrita Cave. 12 records from Planktic foraminifera abundance of Hole 14-138. 70 records from Planktic foraminifera abundance of Hole 84-569A. 76 records from Range table from benthic foraminifers in ODP Hole 139-856A. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 1565 records from (Table 1) Calcareous nannofossil distribution at ODP Site 180-1109 from the Solomon Sea, western Pacific. 225 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE262. 1534 records from Pontaurus. 9 records from Component analysis of TV-guided grab sampler GeoB10071-3. 100 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 119 records from Palynology of a sediment profile from Lake Voulkaria in Greece. 560 records from (Table 3h) Foraminiferal distribution chart of petroleum well Swan-3St. 1048 records from Biodiversidad y dinámica espacio-temporal del ictioplancton de dos sistemas lagunares de la Reserva de la Biósfera de Sian Ka'an. 3538 records from Anfibios del Estado de Veracruz.. 5804 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 5 records from Bryophyte Collection of Shizuoka Prefecture Museum of Natural History. 10 records from (Table 3) Cell number of the main taxonomic groups of phytoplankton and their percentage in total number of phytoplankton in the water column in the northern subtropical Pacific. 180 records from (Table 8) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-217. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 10928 records from TRTE Herbarium (TRTE). 44 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE293. 600 records from (Table 2) Percent distribution of calcareous nannofossils at ODP Hole 125-782A. 1289 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 2073 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 2 records from Akita Prefectural Museum＋Specimens of Phylum Porifera of Akita Prefectural Museum. 115 records from Mollusca specimens of Kuroshio Biological Research Foundation. 2427 records from Ibaraki Nature Museum, Mollusk collection. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 2054 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of DSDP Hole 38-338. 4433 records from Röntgenarchiv Wilhelm Stürmer - SMF. 1 records from Pelops tardus. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 6450 records from Meiobenthos of subtidal sandbanks on the Belgian Continental Shelf (EurOBIS). 6019 records from iziko South African Museum - Mollusc Collection (AfrOBIS). 1202 records from (Table 18) Ranges of benthic foraminifers through the Neogene in DSDP Hole 23-219. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 10189 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 15328 records from SOMBASE. 11209 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 100733 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 63084 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1996) (AfrOBIS). 5 records from Analyses of the recent components of sediment core PS1400-4. 1036 records from Benthic foraminifera distribution of sediment core ASV1200. 15312 records from UCM Mammal Collection (Arctos). 316 records from Moss species from Heard Island, 1987 and 2000. 234 records from Danisco-Wiese. 214 records from Mißmahlsche Anlage. 74 records from Planktic foraminifera abundance of Hole 62-465A. 796 records from Planktic foraminifera abundance of Hole 42-372. 332 records from Planktic foraminifera abundance of Hole 9-79. 52 records from Range table from planktonic foraminifers in ODP Hole 151-913A. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 12 records from Phytoplankton abundance in surface water in October 1995, Chimbote, Peru. 1182 records from (Appendix A3) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1212B in the central Pacific. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 122571 records from Herbier de la Guyane. 26 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto48-56. 157 records from (Table 6) Live benthic foraminifera in sediment core SO130-291MC. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 4599 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 16098 records from The Bat Conservation Trust - The BCT/MTUK Bats & Roadside Mammals Survey. 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 3 records from Analyses of the recent components of sediment core PS1215-2. 1003 records from BÜG. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 224 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 80 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 61 records from Steinbruch Pluwig. 640 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 62 records from Occurrence of mammalia relicts at site Zawalona Cave. 692 records from Planktic foraminifera abundance of Hole 40-360. 878 records from Planktic foraminifera abundance of Hole 84-568. 201 records from Planktic foraminifera abundance of Hole 32-313. 518 records from Foraminifera abundance of Hole 21-208. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 877 records from Benthic foraminifera abundance of Hole 40-362. 25 records from (Fig. 9B) Compiled data of profile Pré-Guittard, SE France. 3630 records from Benthic foraminifera distribution of sediment core GIK17957-2. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 405 records from Freiburger Netzwerk Artenvielfalt. 897 records from Diatom and foraminiferal samples from surficial sediments of Prydz Bay, Antarctica. 2500 records from Zooplankton (NSMK-ZP). 5778 records from Vascular Herbarium, NMBU. 9349 records from Harriet Irving Botanical Gardens (HIBG). 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 28420 records from Lichen Collection - University of Washington Herbarium (WTU). 1 records from Abundance of benthos infauna at station GIK23004-3. 1137 records from Plantas Acuáticas de la Orinoquía Colombiana. 85449 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Zetes latirostris. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 6100 records from HTSA - Herbário do Trópico Semiárido. 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 72636 records from Insect Collection of Taiwan Forestry Research Institute. 2 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 267 records from Die Milbenfauna der Nordseeinsel Wangerooge. 1 records from Nothrus angulatus. 21 records from Occurrence data of Namibimydas and Nothomydas (Diptera: Asiloidea: Mydidae). 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 3275 records from Quantitative Phytoplankton data from Irish lakes (EPA). 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 27278 records from UAM Entomology Observations (Arctos). 9024 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 25128 records from Royal Museum of Central Africa - Albertian Rift Butterflies (ENBI wp13). 743 records from Fish monitoring data in Lake Kasumigaura. 7585 records from National Barkfly Recording Scheme - Outdoor Psocoptera (barkfly) records for Britain & Ireland, 1850 to present.. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 864 records from (Table T16) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P9-P12. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 19 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mar del Plata (Pugnali, junio 1998). 127 records from Kieppi mammals collection. 755 records from Helgeland Museum, Syrphidae. 246960 records from Vascular Plants, Field notes, Trondheim (TRH). 1 records from New species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Côte d’Ivoire. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 4024 records from Sightings Map of Invasive Plants in Portugal. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 20043 records from Mollusca collection of National Museum of Nature and Science. 3204 records from Faunal Inventory of Morysin Nature Reserve. 89874 records from ecoscope_observation_database. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 177466 records from CAS Entomology (ENT). 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 1 records from Oribates picipes. 63 records from (Data S1) Palynology of ODP Site 119-739. 2172 records from Coleccin de Reptiles. 28370 records from UAM Bird Collection (Arctos). 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 8629 records from National Taiwan University. 76 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 1 records from Nothrus bicarinatus. 9787 records from Finnish Entomological Database: Hymenoptera. 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 57 records from Waldhusener Moor (Lübeck-Kücknitz). 49 records from Dörnberg. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 61 records from BIRDRACE Baumläufer. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 10 records from Microzooplankton abundance and biomass at station TT045_21-25. 1 records from Microplankton counts and carbon biomass at station TT008_6-CTD64. 127 records from Meiobenthic assemblages colonizing artificial soft sediments at 20 m depth in Arctic glacial Kongsfjorden, Spitsbergen, Svalbard - individual number. 51 records from Coccoliths in sediment core PS1295-4. 14 records from Nannofossil abundance of Hole 14-140. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 90 records from Planktic foraminifera counts of sediment core RC13-158. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 108 records from (Fig. 9g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2041. 40 records from Pollen record of sediment core Bokanjacko Blato 1. 16233 records from Crustacea specimens of Toyama Science Museum. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 18940 records from Cowan Tetrapod Collection - Mammals. 3387 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 1000 records from Colección Limnológica del Chocó. 5155977 records from Australia's Virtual Herbarium. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 114 records from Flora. 244 records from WildesMoor bei Schwabstedt. 39 records from Stausee Weiditz. 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 371 records from Bannwald Burghauser Forst. 82 records from BIRDRACE Die Ziegeneier. 101 records from Steinbruch Kronungen. 76 records from BIRDRACE Nachtigallen. 5477 records from Colección de mamíferos de la Universidad del Valle. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 1770 records from Schmidt Museum of Natural History_Birds. 202 records from Total foraminifera counts from multinet M31/3_MSN900. 233 records from Total foraminifera counts from multinet M32/5_MSN976. 138 records from Plasm bearing foraminifera counts from multinet SO119_MSN1278. 84 records from Total foraminifera counts of multinet M12/3_MSN538. 9647 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 155255 records from CAS Invertebrate Zoology (IZ). 89 records from Schulgelände Paul-Gerhardt-Schule. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 26 records from Ostracoda abundance of Hole 13-132. 14 records from Nannofossil abundance of Hole 49-412. 9 records from Diatom abundance measured on water bottle samples at station PS58/048-3. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 671604 records from LACM Vertebrate Collection. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 1634 records from (Table 2) Stratigraphic occurrences of the dinoflagellate cysts in lithologic Subunit IIIB of ODP Hole 120-748C. 55189 records from UWBM Mammalogy Collection. 91633 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1993) (AfrOBIS). 307 records from Schlichemquelle (Tieringen/Meßstetten). 102 records from Muehlenbach bei Friesheim. 83 records from Planktic foraminifera abundance of Hole 14-135. 7693 records from NHM, Heteroptera. 12 records from Art´n Vielfalt im Kinderwald. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 881 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 81 records from Total foraminifera counts of multinet M21/5_MSN728. 50 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1338. 6 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 239 records from Size of planktic foraminifera at CTD station M39/4_376CTD-29. 9 records from Trap data GBN3, 3921 m. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_1-CTD14. 5 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC7. 6 records from Microzooplankton abundance and biomass at station NBP97-08-31-7. 126 records from Mol·luscs d'Andorra. 36 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 18 records from Phytoplankton abundance during G. M. Dannevig cruise GMD91/10. 61 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/362-1. 1351 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 569 records from Distribution of nanoplankton at trap WR2. 124 records from Total foraminifera counts of multinet M12/3_MSN559. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 68 records from Plasm bearing foraminifera counts of multinet M21/5_MSN729. 22 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1337. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 66 records from Calcareous dinoflagellates nominated in grain fraction < 20 µm. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 18 records from Phytoplankton abundance at station Rigel_4_2005-04 in April 2005, Chipana, Chile. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 138 records from Fig. 3. Pollen counts of the PG1756 core from Lake Billyakh. 69 records from Mönchspark. 4 records from Nannofossil abundance of Hole 16-156. 6 records from Nannofossil abundance of Hole 4-30. 24 records from Nannofossil abundance of Hole 8-72. 74 records from Ostracoda abundance of Hole 48-401. 55 records from Nannofossil abundance of Hole 94-609. 79 records from Ostracoda abundance of Hole 34-319. 758888 records from Flora Atlas N.T.. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 181 records from Marine Biological Association - RISC and ALERT Marine Non-Native Species (Chinese Mitten Crab, Wakame and Carpet Sea Squirt) Records. 345 records from Cretaceous nannofossils in profile Serre Chaitieu, SE France. 40 records from Nannofossil abundance of Hole 47-398. 2 records from Nannofossil abundance of Hole 6-57A. 73 records from Nannofossil abundance of Hole 3-15. 2 records from Nannofossil abundance of Hole 74-526C. 22 records from Nannofossil abundance of Hole 39-355. 7 records from Nannofossil abundance of Hole 27-259. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 51 records from Nannofossil abundance in sediment core PS1293-4. 785 records from (Appendix I) Distribution of Quaternary nannoflora at DSDP Site 90-594 east of South Island, Southwest Pacific. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 1127 records from Planktic foraminifera counts of sediment core RC14-35. 326 records from Planktic foraminifera counts of sediment core V14-77. 69 records from Planktic foraminifera counts of sediment core V19-19. 129 records from Dinoflagellate cysts from sediment core PS2458-4. 61 records from BIRDRACE Bergische Ornis. 213 records from Amphibian and Reptile (JNHM-AR). 118 records from Antarctic Amphipoda. 144 records from (Table 7) Distribution of ostracode species in surface sediments of the central Laptev Sea. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 72 records from (Table 1) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-682A. 13 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/046-3. 18 records from Meiofauna abundance in sediment core 13368-015. 414 records from (Table A a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-22 at 2000 m water depth. 70 records from Planktic foraminifera counts of sediment core RC13-153. 20691 records from Cladocera and Copepoda. 146494 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 6256 records from Colección Ictiológica del Río Bravo en México (UANL). 160 records from (Table 5) Distribution of Pleistocene to late Oligocene nannofossils in ODP Hole 108-659A. 204 records from Dinoflagellates and pollen of the Brito-Arctic Igneous Province flora, ODP Hole 104-642E. 48 records from Abundance of phytoplankton in surface water during THALASSA campaign PROSOPE. 863 records from (Table 2) Distribution chart of dinoflagellate cysts and acritarchs from Angles, Southeast France. 4 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 478 records from Parásitos de peces nativos de cenotes de la Península de Yucatán, un ecosistema único en México. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 270 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 248680 records from Swiss National Orthoptera Databank. 299 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 150169 records from UWFC Ichthyology Collection. 18 records from (Table 10) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-686. 429 records from Larval fish at Helgoland Roads in 2004. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 51438 records from Dinoflagelados y Diatomeas del Pacífico tropical mexicano. 3918 records from Reptiles del Estado de Veracruz.. 565 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_2. 22 records from (Table 18) Nannoplankton distribution in sediment core ANS3-T6. 310 records from (Table S1) Dinoflagellate cysts, pollen and spores of sediment core ABC26. 2368 records from Collection Crustacea - SNSD. 21296 records from Nearctic Spider Database. 573 records from Macrobenthic species of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 19760 records from Danish waterbugs (Insecta: Hemiptera-Heteroptera: Gerromorpha + Nepomorpha). 31082 records from MEXU/Plantas Vasculares. 13195 records from Fish Collection of Natural History Museum and Institute, Chiba. 35548 records from Herpetology. 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 764 records from Foraminifera abundance of sediment core AC85-4. 284 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 26 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB6. 430 records from Mammifères sauf Chiroptères du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 67661 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1994) (AfrOBIS). 1608 records from Stable isotope analysis of benthic foraminifera and summer sea surface temperature reconstruction of sediment core PS2489-2. 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 289 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 163 records from Planktic foraminifera abundance of Hole 32-313. 63 records from Foraminifera abundance of Hole 59-450. 37 records from Planktic foraminifera abundance of Hole 27-260. 769 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 40 records from Planktic foraminifera abundance of Hole 14-137. 109 records from Benthic foraminifera abundance of Hole 56-436. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171A. 776 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_98MC. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 1 records from Collection Quaternary Small Mammals IQW. 121 records from Southern Giant Petrel census data within the Australian Antarctic Territory.. 13230 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 4203 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 233 records from Briòfits d'Andorra. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 15 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 1391 records from Open Mosaic Habitat Survey Group - Plants recorded during Open Mosaic Habitat survey in England and Wales (2012). 27264 records from Formidabel; Belgian Ants Database. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 257 records from Kernberge und Umgebung (Jena). 75 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 64 records from Occurrence of mammalia relicts at site Spitalhöhle. 6 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 18918 records from (Table 1) Distribution of benthic and planktonic foraminifers at DSDP Hole 28-270. 59 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 197 records from Benthic foraminifera abundance of Hole 34-321. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 154 records from Range table from benthic foraminifers in ODP Hole 174-1073A. 275 records from Range table from benthic foraminifers in ODP Hole 198-1209A. 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 11 records from Subantarctic Fur sealsat Heard Island, 1987/88. 607514 records from Plant. 3471 records from Collection Foraminifera SMF. 463 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 101480 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 1 records from Oribates humeralis. 801904 records from Queensland Museum provider for OZCAM. 4276 records from Coleção Entomológica Padre Jesus Santiago Moure-Trichoptera (DZUP-Trichoptera). 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 490 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 171B-1051A sediments. 130 records from (Table 16) Calcareous nannofossil occurrences in ODP Hole 130-805B. 882 records from Occurrence of mammalia relicts at site Pestera la Adam. 1 records from Planktic foraminifera abundance of Hole 8-72. 2357 records from Foraminifera abundance of Hole 17-167. 4917 records from (Table 1) Distribution of planktonic and selected benthic foraminifers from DSDP Site 87-582. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 1 records from Microfossil abundance of Hole 35-323. 645 records from Phytoplankton abundance in surface water in March 1997, Ilo, Peru. 480819 records from KTP Ring Data. 33 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (2000m section). 49812 records from Seaweeds of Ireland. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 194 records from (Table S2) Coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 230 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 4153 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 51499 records from NRM-Fishes. 1078 records from Fishes of the Congo River 2010 Expedition. 16 records from Two new emerald geometrid species of Telotheta Warren from Ecuador and Bolivia (Lepidoptera: Geometridae, Geometrinae, Lophochoristini). 51739 records from Crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8330 records from Nijmegen Natural History Museum (NL) - Herbarium. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 98 records from Planktic foraminifera abundance of Hole 74-528. 70 records from Exotic terrestrial flatworms, Macquarie Island. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 281250 records from Quadrige. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 31 records from Description of Cathorops mapale, a new species of sea catfish (Siluriformes: Ariidae) from the Colombian Caribbean, based on morphological and mitochondrial evidence.. 54179 records from E. C. Smith Herbarium (ACAD). 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 270 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 41 records from Örtzemündung (Stedden). 71 records from Birdrace-do_elster_Dortmund. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_11-CTD132. 11 records from Phytoplankton abundance at station Sechin_2003-11-06_2, Casma, Peru. 34 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 1576 records from MfN - Trace fossils. 46 records from Smear slide analysis on sediment core GeoB4216-1. 4 records from Nannofossil abundance of Hole 60-454A. 42788 records from Merseyside BioBank - North Merseyside Insects (unverified). 598 records from (Table 5) Distribution of foraminifera in the Miocene section of ODP Hole 133-826A. 173961 records from Estonian Nature Observations Database. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 34392 records from Water Beetles of Ireland. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 456299 records from CAS Botany (BOT). 42507 records from Bird Collection of Museum and Institute of Zoology PAS. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 485 records from National Taiwan Ocean University. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 632 records from MVZ Hildebrand Collection (Arctos). 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 79 records from Plasm bearing foraminifera counts of multinet M26/1_MSN844. 85 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 115 records from (Table 4) Relative abundances of benthic foraminifera in ODP Hole 128-799B. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 119366 records from The digitization of plant specimens of NTU. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 94 records from Plasm bearing foraminifera counts of multinet M12/3_MSN557. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 44 records from Total foraminifera counts of multinet M21/5_MSN736. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 22853 records from Bryophyte herbarium, Oslo (O). 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 3 records from Nannofossil abundance of Hole 51-417B. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 37664 records from H.A. Stephens Herbarium. 86 records from Naturerlebnisraum Koppelsberg (Plön). 46528 records from Atlas of Danish Fishes. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 647 records from Planktic foraminifera counts of sediment core V29-172. 896 records from (Table 4) Distribution of the large, few-chambered Globigerinelloides species in the Cismon core. 1032 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 72 records from (Table 3) Abundance of living foraminifers in bottom sediments from the Kandalaksha Bay. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 2243 records from Stable isotopes, diversity and composition of foraminifera in sediment core GeoB3004-1. 272 records from Foraminifera distribution of sediment core LynchII-3. 376 records from Wupperaue bei Kemna (Wuppertal). 1 records from Occurrence of mammalia relicts at site Warsaw. 2294 records from Collection Echinodermata fossil SMF. 1740 records from Monitoring data from the federal state Berlin (Germany). 3107 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 2818 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 2233 records from Chrysomelidae of Poland. 107 records from Total foraminifera counts of multinet M26/1_MSN844. 65535 records from OAC-BIO Herbarium. 35 records from Foraminifera species abundances from tow TT011_15-MOC78. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 461 records from Guadeloupe_Bananier. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 31273 records from SABCA. 27299 records from NCSM Vertebrate Paleontology Collection. 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 49 records from Total foraminifera counts of multinet M42/3_MSN1367. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 16 records from Dinoflagellate cysts of sediments core IOW211660-6. 26 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD44. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_7-CTD82. 22 records from Phytoplankton abundance at bottle station GOM1/6. 6 records from Phytoplankton abundance in surface water in 2005, Ancon, Peru. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 8 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 34 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 264 records from Planktic foraminifera counts of sediment core RC12-339. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 57 records from Schulgarten Fichteschule. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 341 records from Size of planktic foraminifera at CTD station PS55/019. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 40 records from Nannofossil abundance of Hole 21-205. 271 records from Collective List of Descriptions about Bacterial Isolates from Korea. 3999 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 1535 records from Mushroom Collection in BCRC. 5 records from The tip of the iceberg: a distinctive new spotted-wing Megaselia species (Diptera: Phoridae) from a tropical cloud forest survey and a new, streamlined method for Megaselia descriptions. 138 records from Planktic foraminifera abundance of Hole 26-250A. 83 records from Planktic foraminifera abundance of Hole 40-361. 152 records from Range table from planktonic foraminifers in ODP Hole 146-889A. 132 records from Range table from planktonic foraminifers in ODP Hole 177-1089A. 3 records from Collection Aves fossil SMF. 156 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 175 records from PSUZC-Rodents Collection. 2443 records from Cnidaria MZS. 779 records from Guadeloupe_Ananas. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 44 records from "Schlechteberg" Ebersbach/Sa.. 103 records from BIRDRACE federleser. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 137 records from Planktic foraminifera counts at CTD station PS55/019. 1 records from Microzooplankton abundance and biomass at station TT054_17-22. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD5. 11 records from Phytoplankton abundance at station Casma_2003-03-13_1, Casma, Peru. 74 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/395-1. 292 records from (Table A1) Calcareous nannofossil of the Middle Cenomanian Event in ODP Site 207-1260. 171 records from Sahrbachtal Kreis Ahrweiler. 32077 records from MfN - Fossil invertebrates Ia. 19 records from Smear slide analysis on sediment core GeoB4214-1. 7 records from Nannofossil abundance of Hole 9-78. 49 records from Nannofossil abundance of Hole 80-548. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 297 records from Planktic foraminifera counts of sediment core RC14-7. 58 records from Planktic foraminifera counts of sediment core V28-122. 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 908 records from Spider (JNHM-SP). 24 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 93 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 75 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 10 records from Abundance of radiolaria at station UT99-5-1. 487 records from Geometry of coccolith Coccolithus pelagicus in sediment core K708-007. 71 records from Nannofossil abundance of Hole 64-478. 45 records from Nannofossil abundance of Hole 64-481A. 4 records from Nannofossil abundance of Hole 9-80A. 56 records from Nannofossil abundance of Hole 82-558A. 27 records from Composition of the medium silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 303 records from (Table 4) Distribution of sphenoliths at DSDP Site 82-563 in the North Atlantic. 1610 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 6321 records from Colección de Anélidos Poliquetos del Pacífico Mexicano (UANL). 14017 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 1 records from Der Kreuzenzian und sein Bläuling. 13461 records from Plant (JNHM-PL). 3968 records from Antarctic Jellyfish. 27812 records from Collection Crustacea - ZMB. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 299 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE272. 436 records from Larval fish at Helgoland Roads in 2005. 16 records from Seawater carbonate chemistry and processes during experiments with benthic foraminifera Ammonia tepida. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 33 records from Coccolith counts of multinet SO119_MSN1272. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 174 records from Birds (NHCA-BI). 21 records from Pollen data of trap CB2. 1230 records from Distribution of planktic foraminifera and calculated sea surface temperature of sediment core MSM05/5_712-1. 1201 records from Computarización de las Colecciones de Anfibios y Reptiles del Centro de Investigaciones Biológicas de la Universidad Autónoma del Estado de Hidalgo. 2025 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 1032 records from Flora y vegetación de la Sierra de San Carlos en el municipio de San Nicolás, Tamaulipas. 2718899 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 248 records from Orca observations from the shores of Macquarie Island. 87929 records from Herbario de la Universidad de Sevilla, SEV. 156948 records from NBI. 71368 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1987) (AfrOBIS). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 3634 records from Herpetological collection of National Museum of Nature and Science. 13478 records from Herp Collection. 66 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-5. 51 records from Schrebergarten Düsseldorf Oberkassel. 3290 records from (Figure 8) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 15-35. 26515 records from Natal Museum - Mollusc Collection (AfrOBIS). 5 records from Analyses of the recent components in the sand fraction of sediment core PS1222-1. 149 records from Biotop Binsenwiesen (Wehrheim/Taunus). 6 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 540 records from (Figure 2a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3209. 1 records from Occurrence of mammalia relicts at site Neasham. 5100 records from (Figure 2) Planktonic foraminifera abundance in DSDP Hole 93-603C. 108 records from Planktic foraminifera abundance of Hole 94-611A. 16 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 233 records from Range table from planktonic foraminifers in ODP Hole 180-1115B. 1054 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 31 records from Finnish Entomological Database: Blattodea. 822 records from Isotope tracer experiment: nematode abundance. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 2000 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 71 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832B. 44 records from Distribution of late Neogene age calcareous nannofossils in ODP Hole 111-677A (Table 2). 3950 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 327 records from Elaboración de las fichas técnicas para la evaluación del riesgo de extinción de 18 especies de peces dulceacuícolas mexicanos. 466 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 1824 records from CNAN/Scorpiones. 19063 records from Mammal specimens. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 3139 records from Foraminifera and stable isotopes of sediment core PS2076-3. 177 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 980 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 5 records from Analyses of the recent components of sediment core PS1014-1. 47 records from Antarctic Euphausiacea occurrence data from Norwegian Antarctic Research Expedition 1979. 452 records from Gelände des IVL (Zeckern). 286 records from schulgarten. 3 records from Planktic foraminifera abundance of Hole 17-166. 2109 records from Helmintos de peces dulceacuícolas de México. 5918 records from Catálogo y recopilación de datos científicos de los lepidópteros nocturnos de México, pertenecientes a cinco familias. 3954 records from Ibaraki Nature Museum, Fungi collection. 280 records from (Table 3) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-705A. 287 records from Collection Odonata - SMF. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 25526 records from Marsh Monitoring Program - Amphibians. 52181 records from ANTARCTIC PLANT DATABASE. 37044 records from CIBIO, Alicante:ABH-GBIF. 15709 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 22042 records from SINBIOTA - marine data (OBIS South America, BRAZIL). 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 69009 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 3 records from Analyses of the recent components of sediment core PS1403-1. 1036 records from BUND - Dassower See (Lübeck/Dassow). 66 records from Abundance of radiolaria in surface sediment, Sea of Okhotsk. 66 records from Foraminifera abundance of Hole 55-432A. 85 records from Planktic foraminifera abundance of Hole 28-264A. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 611 records from Planktic foraminifera abundance of Hole 94-608. 525 records from Planktic foraminifera abundance of Hole 94-611C. 1 records from Range table from planktonic foraminifers in ODP Hole 139-856G. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 1974 records from Range table from planktonic foraminifers in ODP Hole 160-967E. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 13438 records from Cameroon National Herbarium. 10 records from UC Davis Department of Anthropology Museum. 127 records from Planktic foraminifera abundance of Hole 14-140. 1012 records from Amphibian and Reptile Conservation - NARRS Data 2007 - 2011. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 102 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 3 records from Benthic foraminifera abundance of Hole 96-621. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2412 records from Ohio University Invertebrate Paleontology Collection. 201529 records from CAS Ichthyology (ICH). 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 11 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 4014 records from Herpetological specimens. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD45. 6 records from Nannofossil abundance of Hole 10-91. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 49 records from NSG Hellbachtal. 2000 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 28628 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 2148 records from Eppingen und Umgebung. 1403 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-205. 160 records from Duck sightings per month, Macquarie Island. 4044 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 531 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 205 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 10 records from (Table A) Abundance of species detected in mussel beds within hydrothermal fields on the Mid-Atlantic Ridge. 12 records from Occurrence of mammalia relicts at site Kirkdale Cave. 31 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 147 records from Planktic foraminifera abundance of Hole 23-229. 1556 records from Planktic foraminifera abundance of Hole 7-64. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 182 records from Planktic foraminifera abundance of Hole 21-203. 691 records from Foraminifera abundance of Hole 24-236. 539 records from (Table 1) Abundances of Discoaster species in ODP Hole 130-806C. 168 records from Range table from planktonic foraminifers in ODP Hole 155-942B. 650 records from Range table from planktonic foraminifers in ODP Hole 155-946A. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 1 records from Abundance of benthos infauna at station GIK23037-3. 28222 records from Reptile Specimens. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 325 records from Triebesbach (Zeulenroda-Triebes). 1 records from Planktic foraminifera abundance of Hole 54-428. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 15555 records from Biological Records Centre - Coccinellidae Data. 293 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 1924 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 760 records from Carabidae of Wales and England. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Donacobiidae. 319 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 1 records from Emesopsis infenestra Tatarnic, Wall & Cassis, 2011 (Heteroptera: Reduviidae), genus and species new to New Zealand. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 2577 records from Shellfish (WSHN-MS). 9123 records from Flora of Słowiński National Park, Poland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 80 records from Landschaftsschutzgebiet Schmutterwald. 44 records from Wiesen am Treffpunkt Freizeit. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 72 records from Faunal assemblage of sediment core TR149-35. 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 81 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 404 records from Range table from benthic foraminifers in ODP Hole 189-1171D. 38 records from Dinoflagellate abundance of Hole 71-512. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 4591 records from WII Herbarium Dataset. 5759 records from EcoRecord - Mammal records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 26990 records from British Lichen Society - BLS Rare and Threatened Lichen Records: England. 1990 records from Seabird 2000. 47036 records from FURB - Herbário Dr. Roberto Miguel Klein. 1160 records from Herbarium J Räsänen. 9552 records from Countryside Council for Wales - UK Biodiversity Action Plan Invertebrate Data for Wales. 2193 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 7 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 7679 records from Herbier CNRST/INERA. 20891 records from Biological Records Centre - Brachycera (Diptera) records from Britain and Ireland to 1990. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 850 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 1 records from Oribates globulus. 31 records from Liether Park (LMS), 6g. 2 records from Pollen analysis of sediment profile GPL0 from Grosser Ploetzensee. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 85 records from Ober-Olmer Wald. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1297 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 6 records from Abundance of two benthic foraminifera species in sediment core 12930-007. 7 records from (Table 5A) Neogene distribution of calcareous nannofossils at DSDP Hole 43-386. 155 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2007. 49354 records from SDNHM Birds Collection. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 712 records from Herbier G. Garapin (BOUM). 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 151 records from Molluscan fauna of Gueishan Island of Taiwan. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 1911651 records from Consortium of California Herbaria. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 78 records from Birdrace-Die_Laufenten-Braunschweig. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 192 records from "Schwarzwassertal" bei Pobershau. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 149 records from Total foraminifera counts from multinet M31/2_MSN888. 74 records from Total foraminifera counts of multinet M21/4_MSN699. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 171 records from Total foraminifera counts of multinet M21/2_MSN652. 36115 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 81 records from Birdrace-Die_Ornithomaten-Herford. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 20 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5115-1. 7 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 10 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_15-CTD152. 125 records from Range table from ostracoda in ODP Hole 143-866B. 275832 records from Northern Territory Museum and Art Gallery provider for OZCAM. 734 records from Mammals (NSMK-MM). 3253 records from Inventario florístico de la Sierra de Huautla, Morelos. 2810 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 479 records from CBS Bacteria Database. 189 records from Fish larvae biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 5 records from Analyses of the recent components of sediment core PS1216-1. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 593 records from Mamíferos voladores laguna El Tinije. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 36 records from Sedimentological investigation on core V15-168. 94 records from Landschaftsschutzgebiet Buchhorst 4. 40 records from Total foraminifera counts of multinet M21/4_MSN716. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 11 records from Microzooplankton abundance and biomass at station TT045_11-2. 1 records from Microplankton counts and carbon biomass at station TT011_9-CTD115. 3 records from Sarcodine counts and carbon biomass at station TT011_3-CTD33. 1 records from Heckenstreifen am Zehntbergweg. 34 records from Phytoplankton abundance at bottle station A8/2. 14 records from Nannofossil abundance of Hole 60-456. 125 records from (Appendix) Benthic foraminiferal abundance at DSDP Hole 71-511. 2 records from Nannofossil abundance of Hole 24-234. 17 records from Coccoliths in sediment core PS1527-2. 235 records from PeECE III - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway, 2005. 345 records from (Table T2) Biogenic and mineral composition of sediments cored in Vaale, Schleswig-Holstein. 26493 records from Collection Vermes - ZMB. 67112 records from Ehime University Coleoptera Collection. 121 records from Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 1574 records from Lepidoptera - SNSD. 1185 records from (Appendix A) Foraminifera and stable carbon and oxygen isotope record of ODP Site 105-646. 3359 records from (Appendix) Relative abundance of planktonic foraminifera in ODP Site 138-846 late Quaternary sediments. 468 records from Distribution of planktic foraminifera in surface sediment samples from cruise SO136. 26936 records from The Brown University Foraminiferal Data Base (BFD). 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 143 records from Planktic foraminifera counts at CTD station PS55/025. 2 records from Microzooplankton abundance and biomass at station TT050_11-4. 4 records from Abundance of nematoda in sediment profile M3/1_031 from the Iberian deep sea basin (Table 5). 4 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 43-384. 92 records from Wiesen in der Grünen Mitte. 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 2 records from Nannofossil abundance of Hole 1-6A. 2 records from Nannofossil abundance of Hole 9-77A. 2 records from Nannofossil abundance of Hole 9-79A. 40 records from (Table 3) Distribution of calcareous nannofossils in DSDP Hole 92-598. 48 records from (Appendix 7) Pollen analysis of soil profiles obtained in the Nagqu area. 2077 records from Vascular plant specimens of Iida City Museum. 2702 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 5 records from (Table 7) Paleotemperature estimates for ODP Hole 104-642B. 62 records from (Table S1b) Measured tomographic parameters for Oridorsalis umbonatus during the PETM for ODP Site 208-1262. 154 records from (Table 10) Dinoflagellate cyst species distribution in ODP Hole 112-686B. 14 records from Occurrence of mammalia relicts at site Pavlov. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 1596 records from (Table 14) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-592. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/554-2. 1522 records from Ibaraki Nature Museum, Fish collection. 81490 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1995) (AfrOBIS). 7 records from Analyses of the recent components of sediment core PS1222-1. 41966 records from Tagged Seal Location Data from SOGLOBEC. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 18 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 20 records from Range table from nannofossils in ODP Hole 199-1217B. 302 records from Kohlstattbrunnental. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 88055 records from PACA-AGP - Herbarium Anchieta. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 57 records from Heidesee / Halle. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 141 records from Total foraminifera counts of multinet M21/1_MSN614. 6 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 4 records from Nannofossil abundance of Hole 3-16. 346 records from (Table C a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-23 at 3000 m water depth. 500 records from Plant (KOBG_PL). 1499 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 32 records from (Table 1) Distribution of calcareous nannofossils in the Eocene of ODP Hole 113-689B. 1090 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 811 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 144 records from Endocast Collection -CONICET- Argentina. 1657 records from Phragmites of Canada. 2960 records from Herp specimens. 141104 records from Lichen Herbarium Berlin. 1020 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage (Australian Antarctic Data Centre). 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 33 records from Benthic foraminifera abundance of Hole 76-533A. 881 records from Range table from benthic foraminifers in ODP Hole 189-1170A. 10 records from Oberservation of birds at station PS14/157 along 49° West. 593 records from Amphibians and reptiles of Ireland. 819 records from (Table T4) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P7-P8. 106342 records from CSIRO Marine Data Warehouse (OBIS Australia). 57 records from Microzooplankton abundance measured on water bottle samples at station PS58/091-4. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 2599 records from Insecta ZMK. 1508 records from Spider (YCEM-SP). 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE206. 3 records from Pollen analysis of surface samples near sediment core Fiekers Busch. 3166 records from WA. 132 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 15 records from Herdengelhoehle taxa and datings. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 6 records from Oberservation of birds at station PS14/146 along 49° West. 4579 records from Estacion Biologica Donana - CSIC, Anfibios (EBD_HERP). 3942 records from UAFMC Mammals. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 575081 records from Rio de Janeiro Botanical Garden Herbarium Collection. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 320 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 39 records from (Table 1) Constituents of the sand-size fraction of ODP Hole 139-856A. 47 records from Pollen analysis of sediment core T89-16-PC. 14 records from Pollen profile Märchenwald A, Harz, Germany. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 2399 records from Estudio monográfico de la familia Rhamnaceae en México. 1248 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 522 records from (UTCFM) University of Tennessee - Fossil Mammals Collection. 1833 records from DSMZ Fungi. 10607 records from Desmidiaceae Engels. 6926 records from Distribution of planktic foraminifers of core V30-36. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1016-1. 341 records from (Table A.06) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (125-250 µm). 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 498 records from Riedensee. 244 records from Quarrendorfer Landschaftsschutzgebiet. 13607 records from Fundación Miguel Lillo - Colección Ornitológica. 105 records from Occurrence of mammalia relicts at site Sirgenstein. 62 records from Occurrence of mammalia relicts at site Pestera Livadita. 102 records from Planktic foraminifera abundance of Hole 67-498A. 28 records from Hypostomus macushi, a new species of the Hypostomus cochliodon group (Siluriformes: Loricariidae) from Guyana.. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 44 records from Royal Horticultural Society - Pittosporum sucker (Trioza vitreoradiata) records acquired by the Royal Horticultural Society. 171 records from Range table from benthic foraminifers in ODP Hole 171-1052E. 191859 records from herbario. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 246 records from Repatriación del material ictiológico de 12 estados de la República Mexicana, depositado en la colección ictiológica de la Universidad de Tulane, E.U.. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 43356 records from Canadian Museum of Nature Fish Collection. 21680 records from Osaka Prefectural Minoh Park Insects Museum. 2440 records from Colección Nacional de Icnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 28647 records from IndOBIS, Indian Ocean Node of OBIS. 195 records from Visual Plants (144.41.33.158) - Private collection of Eberhard Fischer. 4124 records from Herbario de la Universidad de La Laguna:TFC-Bry. 1182 records from Distribution of planktic foraminifera, factor analysis, SST of sediment core PS2498-1. 66 records from Planktic foraminifera assemblage in sediment core GeoB1113-4. 159 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 2078 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 29 records from (Table 2) Distribution of kummerform and sinistral specimens the planktic foraminifera Contusotruncana contusa in Cretaceous sediments. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 152 records from AKG-Gelände (Bensheim). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 57 records from Occurrence of mammalia relicts at site Tornewton Cave. 27 records from Occurrence of mammalia relicts at site Bettelküche. 15 records from Occurrence of mammalia relicts at site Barrington. 149 records from Benthic foraminiferal abundances from eight sites of the Northwest Australian shelf. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 1 records from On the Chilopoda from Turkey. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1 records from Planktic foraminifera abundance of Hole 39-359. 890 records from Planktic foraminifera abundance of Hole 40-363. 760 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_88MC. 413272 records from DATAVES. 1 records from Conchological Society of Great Britain & Ireland - RISC Non-Native Species Records for Zebra Mussel. 3 records from Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia.. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 104520 records from Recent Invertebrates Specimens. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 104 records from BIRDRACE Erlanger Piepmätzchen. 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 136 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1371. 3 records from Sarcodine counts and carbon biomass at station TT007_3-CTD29. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 21 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 369 records from BIRDRACE Havelland. 40 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500. 7 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB4. 44 records from Planktic foraminifera abundance of Hole 51-417A. 1257 records from Faun. 2571 records from RSPB - Black grouse surveys in Dumfries and Galloway 1980-2005 (RSPB and the Southern Uplands Partnership). 1995 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 375 records from Phthiraptera. 20 records from Heteroptera - SMNG. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 2923 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 103 records from BIRDRACE Die Otzberger. 144 records from Lustbach-Umland. 96 records from "Ahrschleife bei Altenahr". 44 records from Planktic foraminifera abundance of Hole 19-188. 2083 records from Planktic foraminifera abundance of Hole 72-517. 167 records from (Table 6) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-601. 63 records from Range table from planktonic foraminifers in ODP Hole 167-1015A. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 4290 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 191 records from Herbarium specimens of Bamboo collection Prafrance Générargue (BAMBO). 4 records from Pachycondyla nigrita and related species in Southeast Asia.. 101 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0028A. 45809 records from Herpetology Collection - Royal Ontario Museum. 57 records from A new Stomatorhinus (Osteoglossomorpha: Mormyridae) from the Ivindo River, Gabon, West Central Africa.. 43 records from Notes on the snake eels of the genera Apterichtus and Ichthyapus (Anguilliformes: Ophichthidae) of the Central and South Pacific, with the description of a new species.. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 177 records from (Appendix) Ostracodes at DSDP Leg 72 Holes. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 105 records from Natural England - Species Surveillance Project - In-House Pilots records for 2012. 462 records from John Muir Trust - Knoydart Lichens, 1990. 5 records from Arthropoden aus südostalpinen Höhlen.. 7509 records from Perot Museum of Nature and Science. 33 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071F. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 149 records from Naturnahes Tal in Siena. 47 records from Collection Pentastomida SMF. 13 records from Collection Reptilia fossil SMF. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 1212 records from Birds fallen at Danish Lighthouses 1883 through 1939. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 272 records from Neuroptera (Insecta) of Ireland. 2 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 173-1069A. 2467 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 1 records from Pelops ureaceus. 994 records from Biological Records In Essex - Bat records for Essex from 1971 - present.. 3061 records from Artròpodes d'Andorra. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 165366 records from KUBI Mammalogy Collection. 382 records from Reptilia ZMK. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 4399 records from Fundacin Miguel Lillo - Coleccin Entomolgica. 1808 records from Fongs d'Andorra. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM6. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 103 records from Birdrace-Die_Nachtigallen-Herford. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 127 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 179 records from Total foraminifera counts from multinet M31/3_MSN906. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 253 records from Mosquitoes (Diptera: Culicidae) of Ireland. 66 records from Total foraminifera counts from M35/1_MSN1059. 49 records from Total foraminifera counts of multinet M10/2_MSN238. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 49 records from Plasm bearing foraminifera counts of multinet M26/1_MSN845. 94 records from Plasm bearing foraminifera counts of multinet M21/2_MSN647. 8291 records from Ireland's BioBlitz 2012. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 100 records from Feriendorf Ober-Seemen. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 2 records from Concentration of siliceous microplankton in surface sediments, brine. 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 279 records from Koleopterologen am Bausenberg. 212 records from Nanoplankton abundance at station GeoB2017-1. 2392 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 4178 records from ARC- Plant Protection Research Institute, National Collection of Arachnida. 33944 records from Aranzadi Zientzi Elkartea. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 9 records from Occurrence of mammalia relicts at site Siebenlinden 1. 10 records from Occurrence of mammalia relicts at site Aveley. 4 records from Planktic foraminifera abundance of Hole 23-223. 201 records from Planktic foraminifera abundance of Hole 11-103. 6 records from Taxonomic notes and distribution extension of Durga Das’s leaf-nosed bat Hipposideros durgadasi Khajuria, 1970 (Chiroptera: Hipposideridae) from south India. 354 records from Microfossil abundance of Hole 35-323. 182 records from Benthic foraminifera and algae abundance of Hole 81-554. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 3768 records from Eggs Specimen. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 11251 records from Herbarium areqvipense (HUSA). 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 127 records from Birdrace_Schräge_Vögel-Herford. 46 records from Hainbachtal in Oelsnitz/V.. 9 records from Willersalpe. 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 4 records from Schulbiotop und Brigach (Villingen). 53 records from Bad Bodenteicher Heide. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 199 records from Planktic foraminifera counts at CTD station M39/4_357CTD-15. 137 records from Abundance of planktic foraminifera at CTD station M39/4_352CTD-11. 137 records from Abundance of planktic foraminifera at CTD station PS55/030. 209 records from Palynomorpha in sediment core IK9373-10 from the Laptev Sea. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC5. 118 records from Phytoplankton abundance at Station Sechin_EP2 in 2002, Casma, Peru. 9 records from Phytoplankton abundance at station Sechin_2003-12-10_1, Casma, Peru. 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 32 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2157-3. 23048 records from Herpetology Collection. 8 records from Die Bachspezies 2008/2009. 545 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 668 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 435 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 19 records from Nannofossil abundance of Hole 31-298. 87 records from Nannofossil abundance of Hole 4-31. 553 records from Planktic foraminifera counts of sediment core V23-91. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 665 records from Collection Echinodermata - ZMB. 1808 records from Ant'Phipoda Database (New records). 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 337366 records from British Lichen Society - BLS Lichen Database: England. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/049-3. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 42 records from Stadtwald Heide. 170 records from Nanoplankton abundance at station GeoB2021-1. 2178 records from Palynological estimation of ODP Hole 189-1172A. 140 records from Distribution of late Turronian planktonic foraminifers in ODP Hole 114-700B. 377929 records from ``South Western Pacific Regional OBIS Data provider for the NIWA Marine Biodata Information System``. 11926 records from Crispin S. Guppy Collection. 362 records from Northern Forestry Centre Arthropod Collection, Edmonton. 12730 records from Banc de dades de biodiversitat de Catalunya-MolusCat. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Helmut Dalitz. 25793 records from NCOS1959_Crustacea (OBIS China). 9195 records from Shellfish Specimens of Miyazaki Prefecture Museum of Nature and History. 1032 records from Percentages of planktonic foraminifera species in sediment core RC24-1. 1435 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-345. 1 records from Results of palynological analysis of Hole 302-M0001A. 64 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 9136 records from “Endemic Species Research Institute Moth Survey” Dataset. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 505723 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 11438 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 1998 records from Aves de la cuenca media del río Bogotá. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 9955 records from Benthic foraminifera abundance in counts of Hole PRAD1-2. 7 records from Abundance of radiolaria at station UT99-22-1. 121 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 1864 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 17266 records from Biological Records Centre - Caddisfly (Trichoptera) records from Britain and Ireland to 2003. 4 records from Nannofossil abundance of Hole 4-29. 63 records from Nannofossil abundance of Hole 7-62A. 6 records from Nannofossil abundance of Hole 7-63. 47 records from Nannofossil abundance of Hole 49-407. 57 records from Nannofossil abundance in sediment core PS1311-4. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 724 records from Planktic foraminifera counts of sediment core V29-64. 9601 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 19 records from Exkursion in der Ehrbachklamm/ an den Erbach. 56 records from Nemertini - SMF. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 165 records from (Table 1) Palynomorph concentrations in ODP Hole 105-646B samples. 15 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 3 records from Akita Prefectural Museum＋Sentipedes Specimens of Akita Prefectural Museum. 3635 records from Raw counts of dinoflagellate cysts in several IODP and DSDP holes. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 30153 records from Kashihara City Museum of Insect. 4 records from Distribution of meiobenthos in sediment core M19_216-2 of the northeastern Atlantic (Table 1). 113 records from (Table 5) Ostracod assemblages of sediment core 9407. 2 records from Nannofossil abundance of Hole 6-58. 9 records from Nannofossil abundance of Hole 26-255. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 22751 records from Lepidopteran specimens of Iwate Prefectural Museum. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 3 records from Casuarinicola australis Taylor, 2010 (Hemiptera: Triozidae), newly recorded from New Zealand. 813 records from Foraminifera abundance of Hole 64-479. 50 records from Planktic foraminifera abundance of Hole 11-106. 83 records from Range table from planktonic foraminifers in ODP Hole 139-858A. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 403738 records from Marine Conservation Society - Seasearch Marine Surveys. 360 records from (Figure 1c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3192. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 2368 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 24 records from (Table 6) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-660A. 8 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE206. 17 records from (Table 2h) Nannofossil distribution chart of petroleum well Swan-3St. 350 records from (Table 3b) Foraminiferal distribution chart of ODP Hole 122-761B. 48 records from Pollen counts of sediment core GeoB9503-5. 11 records from Palynological investigation of profile Tso Kar. 2008 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 8089 records from Los díptera hematófagos y taxa relacionados de dos áreas protegidas del estado de Yucatán, México (Insecta). 1 records from Akita Prefectural Museum＋Brachiopods Specimens of Akita Prefectural Museum. 2676 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 15 records from Description of lithologic section units of IODP Hole 325-M0036A. 342 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 62258 records from Herbarium Senckenbergianum (FR) - Fungi. 470 records from MfN - Isoptera Collection. 23146 records from BC Coastal Waterbird Survey. 59406 records from PIROP (Shipboard Surveys). 3021 records from IBB bacterial database. 28 records from (Table 2) Distribution of late Eocene calcareous nannofossils in ODP Hole 149-897C. 1 records from Miriapodi di alcune grotte della Campania. 113941 records from Pacific Ocean Shelf Tracking (OBIS Canada). 13570 records from Royal Botanical Gardens Herbarium. 2410 records from European Lepidoptera Observations by Donald Hobern. 93 records from CCUG Microorganisms databases(Fungi). 62125 records from UCLA Donald R. Dickey Bird and Mammal Collection. 11622 records from French Grapevine Genetic Resources Center. 407594 records from MAL. 3787 records from Abundance of planktonic foraminifera in sediment core V12-122. 10 records from Sediment properties of core CD86_07_PC. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-112BX. 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 742 records from (Appendix A) Relative abundances of smaller size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 22 records from Occurrence of mammalia relicts at site Grabschütz. 20 records from Occurrence of mammalia relicts at site Kesslerloch. 140 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 42 records from Foraminifera abundance of Hole 24-236. 111 records from Planktic foraminifera abundance of Hole 9-79A. 1347 records from (Table 16A) Occurrences of planktonic foraminifers in DSDP Hole 90-594, samples 594-1-CC through 594-30-CC. 1592 records from Range table from planktonic foraminifers in ODP Hole 139-856A. 85 records from Insektenvielfalt Ahe/Weichelsee. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 944 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 410 records from Planktic foraminifera distribution of sediment core 75KS5. 3 records from Analyses of the recent components of sediment core PS1010-1. 294 records from Naturgarten Langenholtensen. 121 records from Birdrace_Deutschlands_enthusiast.Vogelkucker-Münster. 235 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D4. 20 records from Occurrence of mammalia relicts at site Picken´s Hole. 118 records from Planktic foraminifera abundance of Hole 17-165A. 197469 records from UMMZ Herpetology Collection. 172 records from Foraminifera abundance of Hole 59-448A. 166 records from Planktic foraminifera abundance of Hole 9-82A. 59 records from Planktic foraminifera abundance of Hole 28-266. 39 records from Planktic foraminifera abundance of Hole 28-265. 12 records from Foraminifera abundance of Hole 60-459. 774 records from Planktic foraminifera abundance of Hole 80-549A. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 176 records from Planktic foraminifera abundance of Hole 62-463. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 78 records from Range table from planktonic foraminifers in ODP Hole 169-1035E. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 96 records from Range table from planktonic foraminifers in ODP Hole 145-883B. 131 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 366 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 12 records from Range table from planktonic foraminifers in ODP Hole 182-1133A. 116 records from Range table from benthic foraminifers in ODP Hole 198-1213B. 258 records from Range table from benthic foraminifers in ODP Hole 144-877A. 40 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1072A. 228 records from Phytoplankton abundance in surface water in September 1996, Paita, Peru. 142 records from (Table 3) Distribution of benthic foraminifers in middle Miocene sediments of ODP Hole 182-1134A in the Great Australian Bight. 11 records from Oberservation of birds at station PS14/145 along 49° West. 2980292 records from DOF. 202194 records from Tulane University Museum of Natural History. 2 records from Abundance of benthos infauna at station GIK23043-2. 751 records from (Table T5) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1212B, Shatsky Rise, Pacific Ocean. 1188 records from Countryside Council for Wales - Squirrel Collation for Wales. 29488 records from Animal Sound Archive. 40 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Apodidae. 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 1 records from On centipedes (Chilopoda) of Albania, 2. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 24 records from Range table from planktonic foraminifers in ODP Hole 146-889B. 13 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 195767 records from National vegetation diversity inventory and mapping plan. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 6062 records from Lichens of Knyszyn Forest. 196 records from (Figure 4) Distribution of dinoflagellates in ODP Hole 129-802A. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 1733 records from Birds collection of Abiko City Museum of Birds. 43 records from Diatom assamblage in samples from sediment trap NB6. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD61. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/043-2. 68 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 26 records from Coccolith counts of multinet M32/5_MSN988. 51 records from Nannofossil abundance of Hole 20-200. 16 records from Nannofossil abundance of Hole 24-235. 195 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 14 records from Range table from planktonic foraminifers in ODP Hole 182-1129B. 496 records from Range table from benthic foraminifers in ODP Hole 145-887A. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 666 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-908A. 54120 records from Collection Arachnology SMF. 2618 records from MEXU/Agavaceae. 290333 records from AMNH Mammal Collections. 47672 records from Birds (KIDR-BI). 9 records from Austrolebias univentripinnis sp. nov. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the Mirim Lagoon basin, southern Brazil.. 1 records from Nothrus bicolor. 1 records from Oppia glaucina. 2015 records from (Appendix B) Benthic foraminifera extinction group species in combined DSDP Hole 33-317B and sediment core KR9912-PC4. 926 records from Coleoptera types of John Sahlberg. 111991 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 46710 records from Invertebrates of the Gothenburg Natural History Museum (GNM). 3 records from Arthropoden aus südostalpinen Höhlen.. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 2005 records from EcoRecord - Odonata (Dragonfly and Damselfly) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from Oribates coracinus. 1440 records from Museum TwentseWelle (NL) - Fossil Collection. 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 6776 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Diptera Records up to Dec 2011. 17129 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 650 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anatidae. 2546 records from The atlas of butterflies in Kraków. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 6855 records from Echinoderm collection of National Museum of Nature and Science. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 14 records from Benthic foraminifera abundance of Hole 96-620. 374 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_91MC. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 5406 records from Colección de Mastozoología. 27753 records from Fungi collection of the University of Eastern Finland. 36 records from Norwich Reptile Study Group - Norwich Reptile Study Group Records for 2010. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 193 records from The velvet spiders: an atlas of the Eresidae (Arachnida, Araneae). 184611 records from The Flora of County Waterford. 1615 records from BoGART. 326 records from Colección nacional de palmas de Colombia - JBQ. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 39 records from ECOCEAN MantaMatcher. 71 records from Bolzplatz. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 51 records from Steinbachtal (Würzburg). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 100 records from BIRDRACE Stuttgart 100 trööt. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1045. 148 records from Total foraminifera counts of multinet M21/2_MSN643. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 3 records from Sarcodine counts and carbon biomass at station TT007_4-CTD39. 401 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1768-8. 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 1942 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 65 records from EcoRecord - Alderfly (Megaloptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 13 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 28 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Pycnogonida.. 8 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE262. 138 records from Pollen profile from Wurzacher Becken. 352 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 7490 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Trawl. 3477 records from Aves laguna El Tinije. 870 records from Percentages of planktonic foraminifera species in sediment core V22-38. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 99 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 7626 records from Naturhistorisches Museum Mainz, Herbarium von Ruprecht Düll. 581 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 43443 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). 41 records from Scottish Natural Heritage - Site Condition Monitoring of Annex II Vertigo species in Scotland. 74 records from (Table 7) Miocene to Pliocene nannofossil range chart for ODP Hole 134-832B. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 859 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 1415 records from Plant observations from Białowieża National Park. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 185 records from Total foraminifera counts of multinet M21/1_MSN606. 4 records from Bayerische Donau - Etterzhausen. 2343 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 325 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE258. 348 records from (Table 2) Distribution of planktonic foraminifera in ODP Hole 183-1136A. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 940 records from (Table 10) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 24-238. 2013 records from Collection Arachnida - SNSD. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 116417 records from Michigan State University Herbarium Lichens. 37240 records from LSUMZ Mammals Collection. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 1393 records from Rancho Grande. 576 records from National Collection of Yeast Cultures,Norwich,UK. 277 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 127 records from Industriegebiet (Kempen). 134 records from Birdrace-Raumpatrouille_Oriolus-Münster. 167 records from Planktic foraminifera abundance of Hole 15-151. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 10317 records from KUBI Ichthyology Tissue Collection. 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 222 records from Total foraminifera counts from multinet M31/3_MSN910. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 2792 records from Birds (UWEP-BI). 282 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 31 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part II. 5 records from Loricifera - SMF. 478 records from EASIANET. 166 records from Foraminifera abundance of Hole 22-213. 11 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 36351 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 285 records from (Table 4) Planktic foraminiferal abundance in Oligocene to Early Miocene sediments of ODP Hole 177-1090E on the Agulhas Ridge, South Atlantic. 2 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071A. 330 records from Phytoplankton abundance in surface water in February 1998, Pisco, Peru. 56685 records from MISS_DC_01MAR2006. 90105 records from Paleobotany Division, Yale Peabody Museum. 75600 records from Herbarium Senckenbergianum (FR). 12147 records from Danish Ants (Formicidae). 15975 records from condoncollection. 2046 records from (Table T3) Benthic foraminfera stratigraphy of ODP Hole 199-1221C sediments. 259408 records from MSB Mammal Collection (Arctos). 65842 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 22 records from Heilpflanzen im Hainbachtal. 39 records from Soolbach-Tal. 23 records from Ackerrain Plönhagen. 555 records from FFH-Gebiet "Calwer Heckengäu". 114 records from BIRDRACE LiLaLau. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 749 records from Total foraminifera counts from multinet M32/5_MSN979. 11 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 122 records from Planktic foraminifera counts at CTD station PS55/043. 151 records from (Appendix A) Abundance of calcareous dinoflagellates of sediment core GeoB2204-2. 1850 records from (Appendix 2) Abundances of benthic forminifera in ODP Hole 113-690B. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_26-4. 11 records from Microzooplankton abundance and biomass at station TT050_21-13. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 1 records from Microplankton counts and carbon biomass at station TT007_3-CTD29. 6 records from Microzooplankton abundance and biomass at station NBP97-03-06-8. 179 records from Platyhelminth collection of National Museum of Nature and Science. 17 records from Phytoplankton abundance at station Rigel_2_2005-02 in Febraury 2005, Chipana, Chile. 65 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 42 records from Collection Aves - PUM. 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 131 records from Total foraminifera counts of multinet PO247/2_MSN1377. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 12 records from Phytoplankton abundance in surface water in 1993, Ancon, Peru. 7 records from Distribution of meiobenthos in sediment core M23_133 of the northeastern Atlantic (Table 1). 3415 records from Plant Specimens collections of the Kyushu UNniversity Museum. 7 records from Nannofossil abundance of Hole 7-63A. 72 records from Nannofossil abundance of Hole 31-292. 70 records from Nannofossil abundance of Hole 67-497. 4 records from Nannofossil abundance of Hole 85-574. 464 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 1728 records from Saproxylic Beetles of the Tatra Mts.. 909 records from South American Antarctic Marine Biodiversity Literature. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 481 records from (Table 3f) Foraminiferal distribution chart of petroleum well Montara-2. 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 333 records from Revisión del género Zabrotes para México (Coleoptera: Bruchidae). 35 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 918 records from Invertebrate survey, Heard Island 2001. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 191817 records from The Distribution Atlas of Butterflies in Poland. 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 52 records from Benthic foraminifera and phytodetritus species in sediments from DSDP Site 85-574. 3670 records from Royal Ontario Museum - Entomology (ROME). 34 records from annex4. 40 records from Coccolith counts of multinet M32/5_MSN990. 352 records from Ostracoda abundance of Hole 95-612. 128 records from Nannofossil abundance of Hole 4-25. 7 records from Nannofossil abundance of Hole 38-336. 126 records from Nannofossil abundance of Hole 39-357. 36 records from Nannofossil abundance of Hole 14-141. 13 records from Benthic macrofauna abundance of sediment core 12930-073. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 19633 records from Natural History Museum Rotterdam (NL) - Chordata collection. 5 records from Regenwasserabfangbecken Erlenbach. 255 records from (Table 3) Occurrences of ostracodes in ODP Hole 122-763B. 323 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 310 records from (Table 2) Distribution of main species of planktonic foraminifers in Core AMK21-2179, Woodlark Basin. 5298 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 91 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-765C. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 7 records from Nannofossil abundance of Hole 9-82. 1 records from Zetes gilvulus. 49339 records from Environment Agency - Environment Agency Non-native Species records v1. 2073 records from Bryophyte collection of Jyväskylä University Museum. 86 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 854 records from Collection Hunsrückschiefer - SMF. 16 records from Tettigettalna josei (Boulard, 1982) (Hemiptera: Cicadoidea): first record in Spain, with notes on the distribution, genetic variation and behaviour of the species. 85 records from Unterbrucker Weiher. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 82 records from Planktic foraminifera abundance of Hole 14-144A. 71 records from Planktic foraminifera abundance of Hole 15-153. 104 records from Planktic foraminifera abundance of Hole 28-265. 14 records from Planktic foraminifera abundance of Hole 20-199. 675 records from Benthic foraminifera and algae abundance of Hole 81-553A. 72 records from Ostfriesland. 18000 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 25 records from Hemiodus jatuarana, a new species of Hemiodontidae from the rio Trombetas, Amazon Basin, Brazil (Teleostei, Characiformes).. 685 records from Ostracode relative abundances and geochemistry in surface sediments from Lake Ohrid. 4 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4277 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 431 records from Ictiofauna del sistema lagunar costero Chacahua-La Pastoría, Oaxaca. 519781 records from Danish Mycological Society, fungal records database. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 289 records from Summary of ecologically and stratigraphically important foraminifera in surface samples of the NW African continental margin (Table 3). 88 records from Teich Berlin Wuhlheide. 26 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 798 records from Planktic foraminifera abundance of Hole 27-262. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 59 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 140 records from Range table from planktonic foraminifers in ODP Hole 182-1129D. 60 records from Range table from benthic foraminifers in ODP Hole 139-858C. 230 records from Range table from benthic foraminifera in ODP Hole 199-1220B. 5 records from Microfossil abundance of Hole 50-416A. 13596 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 107485 records from Botany Division, Yale Peabody Museum. 430 records from Collection Strepsiptera SMF. 59 records from Main components of radiolarian assemblage at Site 177-1092. 43 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1017. 1 records from First record of Eggplant Mealybug, Coccidohystrix insolita (Hemiptera: Pseudococcidae), on Guam: Potentially a major pest. 2253 records from Irish National Crayfish Database. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 159 records from (Table 1) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-747. 44 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 491 records from (Table 1) Relative abundances of planktic foraminifers in bottom sediments from Core AMK4-316GC. 1170 records from Colección de Cnidarios. 556 records from Distribution of planktic foraminifers of sediment core D117. 1167 records from Macroinvertebrate Data BOKU. 2 records from Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae).. 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 551 records from Foraminifera abundance of sediment core CS73-34. 626 records from (Table 2) Benthic foraminifera distribution in sediment core ASV11-880-3. 187 records from (Table Ib) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 74-528 on the Walvish Ridge, South Atlantic. 286 records from Occurrence of mammalia relicts at site Roc de Combe. 2 records from Radiolaria assemblage in sediment core GIK23400-3. 576 records from Planktic foraminifera abundance of Hole 23-229A. 48 records from Planktic foraminifera abundance of Hole 6-47. 604 records from (Table 7) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583G. 151 records from Planktic foraminifera abundance of Hole 11-104. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 78 records from Aktion - Friedensburg Oberschule. 24 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 3956 records from Royal Saskatchewan Museum Collection. 13708 records from Bohart Museum of Entomology, UCD. 12963 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 325 records from (Table A.07) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (150-500 µm). 115 records from Wismar Bucht coast-watching. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 48 records from Planktic foraminifera abundance of Hole 47-397. 35 records from Planktic foraminifera abundance of Hole 67-499A. 66 records from Klostergarten St Luzen. 242082 records from Carnet en Ligne. 16102 records from EcoRecord - Diptera Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 42488 records from NCSM Herpetology Collection. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 30327 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 31020 records from National Museum of Natural Science. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 51148 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 9997 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 136 records from (Table 7) Ostracod assemblages of sediment core 9408. 6 records from Nannofossil abundance of Hole 60-457. 64 records from Nannofossil abundance of Hole 24-231. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-077. 94 records from Collection Bryozoa - ZMB. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 91 records from Benthic foraminifera abundance of Hole 84-569A. 21 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB07 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MAY-1995-D2. 564 records from Central Scotland Forest Trust - Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 159 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 32 records from Revision of the genus Sinopoda Jäger, 1999 in Laos with discovery of the first eyeless huntsman spider species (Sparassidae: Heteropodinae). 1036 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zone P4. 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 4567 records from Herbarium WRSL, Main Collection. 11004 records from Dataset of Phenology of flora of mediterranean high-mountains meadows (Sierra Nevada). 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 97 records from Döchtbühlwald (Bad Waldsee). 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 52 records from Total foraminifera counts of multinet M21/4_MSN713. 133 records from Total foraminifera counts of multinet PO247/2_MSN1379. 109 records from Phytoplankton abundance at station CD46_1305C#2. 59 records from Schriesheimer Steinbruch. 120 records from Nannofossil abundance of Hole 47-397. 12 records from Ostracoda abundance of Hole 32-306. 6 records from Range table from planktonic foraminifers in ODP Hole 151-912B. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 807 records from (Table 4) Planktonic foraminifer abundance of ODP Hole 162-981A. 72 records from Range table from planktonic foraminifers in ODP Hole 172-1058A. 18 records from Range table from planktonic foraminifers in ODP Hole 175-1080A. 57 records from Range table from benthic foraminifers in ODP Hole 159-960C. 56 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 18 records from Range table from benthic foraminifers in ODP Hole 144-871B. 56 records from Range table from benthic foraminifers in ODP Hole 144-874A. 4 records from Dinoflagellate abundance of Hole 81-554A. 14 records from Microfossil abundance of Hole 29-277. 182 records from Relative abundance of live benthic foraminifera of sediment core M5/2_88MC. 31930 records from Insect specimens database of Shizuoka Prefecture Museum of Natural History. 49 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1008. 89 records from Dixidae (Diptera) of Ireland. 15 records from Pollen analysis of sediment profile MU1 from Muggesfelder See. 3 records from Hornmilben (Oribatida) [pages 213 to 260]. 1794 records from Herbarium BSG Lichenes. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 32 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2002. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 27 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 110 records from Range table from planktonic foraminifers in ODP Hole 182-1132C. 2 records from Benthic foraminifera abundance of Hole 42-374. 9 records from (Tab. 9) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 36-330, Falcland Plateau. 1 records from Pollen and spore abundance of Hole 42-379A. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 1101354 records from Botany (UPS). 2753 records from (Figure 8 a) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-535. 447 records from Orthoptera del Museo de Entomología de la Universidad del Valle. 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 4579 records from Herbarium WRSL, Flora of the Silesia. 1 records from Miriapodi di alcune grotte della Campania. 1 records from Zetes morticinus. 60 records from NABUGEO1. 2 records from Hildener Heide - Spörkelnbruch (Haan). 68 records from Plasm bearing foraminifera counts from multinet M32/3_MSN956. 111 records from Planktic foraminifera counts at CTD station PS55/037. 486 records from Dinoflagellates of sediment core GeoB1523-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-04-1. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 12 records from Nannofossil abundance of Hole 20-200. 467 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Site 202-1237. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1 records from Nothrus convexus. 17 records from (Table 4) Total phytoplankton biomass, biomass of certain algal groups in the upper mixed layer and the water column, and contribution of the algal groups to total biomass of phytoplankton in the southwest Kara Sea on August 9-12, 2007. 540 records from (Table 1) Pleistocene planktonic foraminiferal assemblages at ODP Site 128-798. 3695 records from Distribution of planktic foraminifera in ODP Site 202-1240 samples. 11 records from (Tables S1,2) Stable isotopes in muscle tissue of polar bears (Ursus maritimus) from various regions of the Arctic. 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 7830 records from Mollusca Collection. 266 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 25486 records from Biological Records Centre - Opiliones (Harvestman) Dataset. 12555 records from Natural History Museum Rotterdam (NL) - Plantae collection. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 200579 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): 1999 Atlas Dataset for Great Britain and Ireland. 2312 records from Mycological collection of the National Museum. 8 records from Order Diptera, family Mydidae. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 6997 records from CHAS Vertebrates. 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 141 records from Draubiotop Lavamünd. 54 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 85250 records from Green Plant Herbarium (TRT). 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 253095 records from Lyman Entomological Museum (LEMQ). 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB3708-1. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 9 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 315 records from Size of planktic foraminifera at CTD station PS55/030. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 1575 records from Porifera MZS. 80889 records from Scottish Natural Heritage - Standing Waters Database. 67 records from Relative abundance of coccosphere-units of sediment core GIK23071-2. 27 records from Ostracoda abundance of Hole 42-376. 2 records from Nannofossil abundance of Hole 9-82A. 8684 records from Individual Sightings. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 491 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 238 records from Revision der europäischen Gattungen und Arten der Familie Brachychthoniidae (Acari, Oribatei) Teil 1. Allgemeiner Teil: Brachychthoniidae Thor, 1934. Spezieller Teil: Liochthonius v. d. Hammen, 1959, Verachthonius nov. gen. und Paraliochthonius nov. gen.. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 46954 records from SPSF - Herbário Dom Bento José Pickel. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 34829 records from Instituto Nacional de Pesquisas da Amazônia (INPA) - Fish Collection. 76 records from Birdrace-Birding_for_Nature-Bonn. 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 117 records from Naturschutzgebiet Kochertgraben. 64 records from Issumer Fleuth. 3 records from Blankenfelder See. 248 records from Schulgarten der Volksschule. 34 records from Total foraminifera counts of multinet M21/4_MSN722. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 13325 records from Herbier du Bénin. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 711 records from Odonata collection, NTNU, Trondheim. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 1119094 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 18004 records from Census of the animals of Benin. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 124 records from Wiesenbiotop am Wasserturm. 721 records from IBF Monitoring of Plant Galls. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 206 records from Total foraminifera counts from multinet M31/3_MSN908. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 1984 records from Planktic foraminiferal species counts in GeoB1117-2. 45 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 175 records from Planktic foraminifera counts at CTD station M39/4_361CTD-18. 328 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 1 records from Microzooplankton abundance and biomass at station TT050_2-10. 10 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1 records from Phytoplankton abundance at station Rigel_3_2005-08 in August 2005, Chipana, Chile. 16 records from Phytoplankton abundance at station Casma_2003-03-27_1, Casma, Peru. 234 records from Clyde River Foundation - Allis Shad (Alosa alosa) distribution for Scotland, historical to present. 1371 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 827 records from Schatzinsel Norderney. 75 records from Abundance of microzooplankton measured on water bottle samples during POLARSTERN cruise ANT-X/6. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 35 records from Phytoplankton abundance at bottle station A3/66A. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 6 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 197 records from Coleoptera identified from the Horton Kirby site, near London. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 193 records from Geometry of coccolith Coccolithus pelagicus in sediment core GIK23065-3. 5 records from Nannofossil abundance of Hole 34-320A. 965 records from Northumberland Wildlife Trust - Squirrel Records for 2002 - 2005. 4 records from Nannofossil abundance of Hole 4-31. 2 records from Nannofossil abundance of Hole 20-199. 5 records from Nannofossil abundance of Hole 74-529. 23 records from Coccolith counts of multinet SO119_MSN1303. 47 records from Nannofossil abundance of Hole 64-479. 2 records from Nannofossil abundance of Hole 1-5. 5 records from Nannofossil abundance of Hole 29-280. 88 records from Nannofossil abundance of Hole 40-362. 10 records from Ostracoda abundance of Hole 44-390. 6 records from Nannofossil abundance of Hole 55-430B. 109 records from Broadland Environmental Services Limited - Reptile distribution along the River Bure, Broadland (2010). 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/061-3. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 279 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 175 records from (Table 3) Benthic foraminifers in the surface sediment layer of the southern Laptev Sea. 945 records from (Appendix D) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748C. 2803 records from IMEDEA-INSECTA. 9067 records from Atlas Nacional de Anélidos Poliquetos de México (ICMyL-DF, UNAM). 27 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 4825 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 3362 records from Coimbra Collection of Algae. 1 records from On the Chilopoda from Turkey. 16 records from Nannofossil abundance of Hole 24-236. 260 records from Range table from ostracoda in ODP Hole 144-873B. 23 records from Meiofauna abundance in sediment core 12930-075. 6909 records from Herbario del Departamento de Biología Vegetal (Botánica) de la Universidad de La Laguna, Tenerife (TFC). 3 records from Antarctic Arrow worms. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 29 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 8072 records from Riqueza específica, distribución y abundancia de aves acuáticas en la ensenada de La Paz, Baja California Sur, México. 1 records from Akita Prefectural Museum＋Specimens of Phylum Nemertea of Akita Prefectural Museum. 55 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV8. 68081 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 58 records from CNIN/Tipos Diptera. 582 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean. 275 records from Wald und Wiese am Buchwald. 8 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 53 records from Planktic foraminifera abundance of Hole 29-278. 415 records from Planktic foraminifera abundance of Hole 29-281. 3 records from Range table from planktonic foraminifers in ODP Hole 139-856E. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 832 records from (Appendix 2) DSDP Site 94-610 ostracode species census data. 1309 records from Mongolian Plant (MMNH-PL). 104 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE241. 46022 records from West African Vegetation Database. 1684 records from MfN Fish Collection, Zoology. 17 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM8. 199 records from Halberg bei Neumorschen. 5 records from Occurrence of mammalia relicts at site Valea Sesii Cave. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 783 records from (Figure 2) Benthic foraminifera abundance of DSDP Hole 93-603C. 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 6943 records from DMNS Egg Collection (Arctos). 1210 records from NPWS Seal Database. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 1932 records from (Table 6) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-852B. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 850 records from Shellfish (NHMK-MS). 99 records from Dorfrand Mauderode. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-52. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 4778 records from SO-Polylist. 357 records from (Appendix D) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in ODP Site 146-893. 375 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 105-646A. 86 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 1042 records from (Table 1) Relative abundances of Maastrichtian benthic foraminifera at El Kef, Part I. 36 records from Pollen profile ADR309. 1 records from Murcia rubra. 23 records from Palynology of profile Füramoos III. 317 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-714A. 23601 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 816 records from Peces de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 576 records from (Table 16) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-710A. 4842 records from (Table 6) Planktonic foraminifer abundance of ODP Hole 162-982B. 33 records from (Appendix 2) Abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core SU81-18. 4417 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 403 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 16600 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 95 records from Überschwemmungsgebiet der Wied. 3 records from Occurrence of mammalia relicts at site Igstadt I. 1686 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 1 records from Benthic foraminifera abundance of Hole 96-624. 140 records from Range table from benthic foraminifers in ODP Hole 139-857C. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Heliornithidae. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 69 records from "Schwarzes Teich" (Waldpark Radebeul). 65 records from LSG "Großes Bruch". 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 1 records from Karpfenteich, Klasse 6d. 107 records from BIRDRACE Borussia Zippammer. 115 records from Total foraminifera counts of multinet M33/1_MSN1028. 11 records from Foraminifera species abundances from tow TT011_2-MOC57. 8 records from Microplankton counts and carbon biomass at station TT012_5-CTD10. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 11737 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 206 records from Folklore and Natural History Museum Amphibia. 650 records from Relative abundance of planktic foraminifera in sediment core K708-001. 1 records from Arthropoden aus südostalpinen Höhlen.. 410 records from Gemeindegebiet Weikendorf (Marchfeld). 622 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 20 records from Occurrence of mammalia relicts at site Stellmoor. 329 records from Planktic foraminifera abundance of Hole 60-458. 279 records from Planktic foraminifera abundance of Hole 11-98. 186 records from Planktic foraminifera abundance of Hole 94-610. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 28648 records from The DNA and Sample Repository at AIT. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 14549 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 106941 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 99300 records from Landesmuseum Kärnten. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 203945 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 726 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 197 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 26 records from Marine Invertebrate Diversity Initiative (OBIS Canada). 19614 records from Mammal specimens. 62592 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1997) (AfrOBIS). 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 495 records from Life Science National Tsing Hua University. 2430 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 1978 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-339. 840 records from (Table T2) Planktonic foraminiferal stratigraphy of ODP Hole 173-1067A sediments. 716 records from Foraminifera distribution of sediment core Chain61-19. 417 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 197 records from Reconstruction of surface water temperature of sediment core GIK12310-4, Cape Barbas, North-West Africa (Appendix Tab. 3). 4 records from Occurrence of mammalia relicts at site Ceremosnica. 278 records from Planktic foraminifera abundance of Hole 39-354. 5173 records from Planktic foraminifera abundance of Hole 15-147. 2444 records from (Table 12A) Occurrences of planktonic foraminifers in selected samples of DSDP Holes 90-590 and 90-590A. 253 records from Planktic foraminifera abundance of Hole 24-233. 43 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 13646 records from Senckenberg - CeDAMar Resource. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 16 records from Inventario de Murciélagos Floreña I, Yopal, Casanare. 1373 records from (Supplementary data 1) Count data of the observed dinoflagellate cyst species from sediment core GeoB10709-5. 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Conopophagidae. 44561 records from Flora of the Stołowe Mts.. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 1 records from Myriopoden von Epirus. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 49637 records from Monitoring data from the federal state Hesse (Germany). 1 records from Murcia trimaculata. 1914 records from Macrophytes_CLF. 37 records from Berlin - Treptower Park / Karpfenteich. 101 records from Naturgrundstück (Eutin). 5 records from Streuobstwiese (Mittelgasse 4). 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 93 records from Haarbach Höfe. 62 records from Lebensraum Dorf. 116 records from Sürther Aue. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 12 records from Range table from benthic foraminifers in ODP Hole 181-1120B. 208 records from Dinoflagellate cysts of ODP Hole 189-1171D. 1 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071B. 44 records from Flora und Fauna in unserer Kita. 8974 records from NCSU_Darwincore. 1 records from Nothrus minimus. 3 records from Nouvelles fourmis de Madagascar.. 1657 records from Reptiles, Amphibians and Fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Australian Formicidae.. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 12 records from Clarias insolitus, a new species of clariid catfish (Teleostei: Siluriformes) from southern Borneo.. 55816 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 7 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 1 records from Contributions a la faune Myriapodologiwue Mediterraneenne. 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 31 records from Siphonaptera. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 66 records from The Neotropical annual killifish genus Pterolebias Garman (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology, and taxonomic revision.. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 191 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s. l., Scelioninae). 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 57879 records from Albany Museum Grant. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 29087 records from Naturalis Biodiversity Center (NL) - Collembola. 1900 records from Fungi Collection. 6 records from Sächsische Schweiz (Pfaffenstein). 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 53 records from BIRDRACE Taubenhaucher. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 97 records from Total foraminifera counts from M35/1_MSN1048. 69 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1379. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 21704 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 58 records from Mamíferos laguna El Tinije. 1476 records from Harvestmen_of_French_Guiana. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 538350 records from iNaturalist research-grade observations. 2413 records from Literature based species occurrence data of birds of North-East India. 155 records from Bammentaler Duft- und Heilkräutergarten. 258 records from BIRDRACE Raumpatrouille Oriolus. 110 records from BIRDRACE Angeliter Ornis. 111 records from Total foraminifera counts of multinet M10/2_MSN219. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 36 records from Total foraminifera counts of multinet FCA97C_MSN1339. 78 records from Total foraminifera counts of multinet M12/3_MSN541. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 11 records from Microzooplankton abundance and biomass at station TT045_7-13. 1 records from Microplankton counts and carbon biomass at station TT011_6-CTD71. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 4 records from Nannofossil abundance of Hole 66-493A. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 145 records from Total foraminifera counts from multinet M32/3_MSN957. 157 records from Total foraminifera counts from M35/1_MSN1069. 2 records from A new trapdoor spider species from the southern Coast Ranges of California (Mygalomorphae, Antrodiaetidae, Aliatypus coylei, sp. nov,), including consideration of mitochondrial phylogeographic structuring. 138 records from Plasm bearing foraminifera counts of multinet M21/2_MSN652. 30 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5130-2. 27 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/041-5. 55 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/590-1. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-15-5. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 29 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 340 records from Phytoplankton abundance and species composition in the Gulf of Naples from February to December 1987. 268 records from Geometry of coccolith Coccolithus pelagicus in sediment core PS1113-1. 2 records from Nannofossil abundance of Hole 3-13. 4 records from Nannofossil abundance of Hole 29-284A. 11 records from Nannofossil abundance of Hole 22-218. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 43 records from MfN - Fossil invertebrates Ib. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 157 records from Planktic foraminifera counts at CTD station PS55/063. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 3 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 11 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 431 records from (Table 6) Benthic foraminiferal community at DSDP Hole 94-611C. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 96 records from Pollen profile from Muscotah Marsh A. 9 records from Nannofossil abundance of Hole 15-150. 2 records from Ostracoda abundance of Hole 13-129. 7 records from Nannofossil abundance of Hole 6-55. 79 records from (Table 2) Quarternary ostracod abundance in sediment core CRP-1. 287 records from (Table 3) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-749B. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 103 records from Mammals (UWEP-MM). 78 records from Mammals (GNHM-MM). 73 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 52 records from (Table 2) Abundance of total planktonic foraminifera and Neogloboquadrina pachyderma in sediment core KNO5103-0029GGC. 75 records from Microzooplankton abundance measured on water bottle samples at station PS58/009-2. 2 records from Zetes laevigatus. 85975 records from Mollusca specimens of Toyama Science Museum. 27 records from Smear slide analysis on sediment core GeoB4212-2. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 10789 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 15455 records from Laboratorio de Entomología y Control de Plagas del Instituto Cavanilles de Biodiversidad y Biología Evolutiva de la Universidad de Valencia: ENV. 243 records from Memorial University Department of Biology Collection. 115365 records from TTU Mammals Collection. 976457 records from EURISCO, The European Genetic Resources Search Catalogue. 900 records from Percentages of planktonic foraminifera species in sediment core V30-36. 188 records from Frauenholz (Holzmaden). 24 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB04 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 38 records from RSPB - Lesser Spotted Woodpecker sample survey in England 2007. 57 records from Planktic foraminifera abundance of Hole 84-566. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 35 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 1196 records from Entomological collection of the National Museum. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 118 records from Abundance of dead benthic foraminifera in sediment core CD86_03_BC4. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 101 records from Nannofossil abundance of Hole 64-476. 2 records from Nannofossil abundance of Hole 25-249. 842 records from (Table 3) Calcareous nannofossil distribution on ODP Hole 117-720A. 3855 records from Icota - Pelagant. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 1877 records from Odonata de la huasteca potosina (insecta). 1789 records from Computarización de la Colección de Microorganismos de importancia acuícola del CIAD, AC. 3559 records from Actualización de bases de datos de peces. 64 records from Establecimiento de la colección de levaduras marinas de México. 1200 records from Invertebrate specimens of Toyama Science Museum. 6290 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 2088 records from Benthic foraminifera of sediment core MD99-2286. 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 140 records from Distribution of planktic foraminifera of sediment core GIK23424-3. 6602 records from Relative abundance of planktic foraminifera in sediment core GeoB1309-2. 34 records from Occurrence of mammalia relicts at site Nikolaushöhle. 69 records from BIRDRACE Pfeifenten. 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 775 records from Insect (GNHM-IN). 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6 records from Folklore and Natural History Museum Mammal. 4288 records from Universitat de Girona: HGI-Cormophyta. 29877 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 243 records from Point Pelee National Park Collection, Canada. 7939 records from Botany registration database by Danish botanists. 894 records from CNAN/Arañas sinantrópicas. 1474 records from CCUG Microorganisms databases(Bacteria). 1322 records from (Table 3) Percentages of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 429 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V32-128. 134 records from National Feral Ferret (Mustela putoris furo) Database. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D2. 3 records from Planktic foraminifera abundance of Hole 54-424B. 288 records from Range table from planktonic foraminifers in ODP Hole 154-929E. 45 records from NSG Dellwiger Wald, Dortmund. 3439 records from MEXU/Flora de Oaxaca. 31747 records from Syrphids of Ireland. 48243 records from Biological Records Centre - Millipede (Diplopoda) records for Britain and Ireland to 2005. 10985533 records from Norwegian Species Observation Service. 280 records from (Table 4) Occurrences of ostracodes in ODP Hole 122-763C. 46 records from (Table 1) Distribution of planktic foraminifera in sediments from Core AMK4-410GC. 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 61 records from Biosphärenreservat Münsinger Alb. 5056 records from Nest census, Windmill Islands 2002/03. 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 46 records from (Table 6) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841B. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 416 records from (Table 3) Benthic foraminiferal genera in DSDP Core 95-612-21-5 and 95-612-21-6. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 132 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fringillidae. 155892 records from Lund Museum of Zoology - Insect collections (MZLU). 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 101 records from BIRDRACE Enger am Spektiv. 145 records from Phytoplankton abundance at station CD46_0405C#7. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 1815 records from RMT Trawl catch from the 1992/93 V6 KROCK voyage. 1241 records from (Appendix 2, Part 2) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-689. 6454 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 191 records from (Table 3) Distribution of principal species of benthic foraminifers in bottom sediments from Core LV28-42-5, Sea of Okhotsk. 950 records from (Table 9) Distribution of planktonic foraminifera in the early Pliocene to Holocene section of ODP Hole 149-900A. 178 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 205599 records from CABI Bioscience Fungus Collection. 1098 records from Mushroom in North Korean (KIDR-MR). 21619 records from Botanical Museum, Copenhagen. Database of type specimens. 146624 records from Plants of Papua New Guinea. 32606 records from TSB Lichen Herbarium. 113 records from Stable isotope analysis on sediment core PS2644-2. 218 records from Planktic foraminifera assemblage in sediment core GIK16396-1. 783 records from RAVON (NL) - Fish observations extracted from Hoek (1890) and Redeke (1921). 16122 records from Colección Herpetológica del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 544 records from (Table AT6) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130B. 118 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 25 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200260. 69 records from BIRDRACE Mathilden-Käuze. 477 records from (Table 3) Relative abundances of planktic foraminifera in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 186 records from (Table 2c) Percentages of energy flow of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 22 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 38 records from Occurrence of mammalia relicts at site Istalloskö. 14 records from Radiolaria assemblage in sediment core GIK23259-2. 432 records from Foraminifera abundance of Hole 60-454. 1787 records from Planktic foraminifera abundance of Hole 80-548. 156 records from Range table from planktonic foraminifers in ODP Hole 155-932B. 74 records from Range table from planktonic foraminifers in ODP Hole 167-1013A. 1649 records from Benthic foraminifera abundance of Hole 47-397. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 208 records from Range table from benthic foraminifers in ODP Hole 144-875C. 264 records from Range table from benthic foraminifers in ODP Hole 146-892A. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 3207 records from UAFMC Herps. 336 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 2222 records from UWYMV Bird Collection (Arctos). 31 records from Düpenauwiesen. 24 records from Planktic foraminifera abundance of Hole 19-189. 584 records from Planktic foraminifera abundance of Hole 11-98. 812 records from Planktic foraminifera abundance of Hole 94-607. 12612 records from (Table 1) Range table of planktonic foraminifers from ODP Hole 166-1006A sediments. 401 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 136 records from Range table from benthic foraminifers in ODP Hole 192-1184A. 167 records from Range table from benthic foraminifers in ODP Hole 171-1049A. 168 records from Phytoplankton abundance in surface water in September 1996, Pisco, Peru. 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 47694 records from Collection Mollusca SMF. 17720 records from Collection Polychaeta SMF. 17 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (2000m section). 31 records from First description of the worker caste of Nylanderia smythiesii (Hymenoptera: Formicidae). 132 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 275 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in Quaternary sediments from ODP Hole 189-1172A. 321 records from (Table T1) Dinoflagellate cyst abundance in ODP Hole 171B-1053A sediments. 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 934 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Japanese Knotweed Survey. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 38 records from Was lebt in der Brutzwiese?. 406 records from (Table 4) Distribution of foraminifera in the Miocene section of ODP Hole 133-816C. 1 records from Oribates facula. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 6529 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 43 records from Relative abundance of planktic foraminifer Globigerinita uvula in core PS1243. 49362 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 6 records from Pollen profile RAA37, Lake Racou, France. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 2174 records from MLZ Mammal Collection (Arctos). 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 9 records from Wiesendreieck Luckenwalde. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 40 records from BUND Naturschutzzentrum St. Julian. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 172 records from Total foraminifera counts of multinet PO247/2_MSN1371. 265 records from Size of planktic foraminifera at CTD station PS55/084-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/012-5. 19 records from (Table T3) Calcareous nannofossil abundance of ODP Hole 189-1170A sediments. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 2994 records from Museu de Ciències Naturals de Barcelona: BGJBB. 27447 records from HAS - Herbário Alarich Rudolf Holger Schultz. 58327 records from Inventaire National du Patrimoine Naturel : Fichier communal des ongulés. 18 records from (Table 2) Abundance, wet biomass, and carbon biomass of all major groups and total phytoplankton in the upper and lower parts of the desalinated water lens and in the layer under the lens in the Kara Sea. 210 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Mimidae. 70 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 308 records from Wangerooge. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 17 records from Hydrolagus mccoskeri sp. nov., a new species of chimaeroid fish from the Galápagos Islands (Holocephali: Chimaeriformes: Chimaeridae).. 145 records from Assemblage of living benthic foraminifera in sediment profile GeoB4909-4. 272 records from Wald am Schloss Wittgenstein Bad Laasphe. 48 records from (Appendix) Abundance of Discoaster brouweri and Coccolithus pelagicus in ODP Site 180-1115 sediments. 4 records from Seodaemun Museum of Natural History Fossil. 2 records from Two new species of Baeus (Hymenoptera: Scelionidae) from southeastern Brazil parasitoids of Anelosimus (Araneae: Theridiidae).. 1 records from Zetes dorsalis. 135 records from Collection Pisces - KAUMM. 1605 records from Hare Survey of Ireland 06/07. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty and Biswas. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 38200 records from Herbario Universidad de Antioquia (HUA). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 11731 records from HAS-Algae - Coleção Ficológica do HAS. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 10866 records from Heteroptera of Ireland. 22 records from Breitkopfbecken (Berlin-Reinickendorf). 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 193 records from Total foraminifera counts of multinet M21/3_MSN663
Keywords: GBIF; biodiversity; species occurrences